Heavy DIY Activities as a Potential Preventative for Stress Urinary Incontinence - Kai Liu; Xiaogang Lian; Ting Wang; Zhu Tao (American Journal of Men's Health)
Physical activity is associated with stress urinary incontinence (SUI). The genetic causality of this association remains unclear. This study used the Mendelian randomization (MR) method to explore the potential causal relationship between physical activity and SUI risk using heavy do-it-yourself (DIY), light DIY, strenuous sports, walking for pleasure, and other exercises as proxies. We selected single nucleotide polymorphisms associated with physical activity from published genome-wide association studies (GWAS). Statistics of SUI come from the GWAS database. MR estimation was performed using the inverse variance weighting method, the MR-Egger method, and the weighted median method. Sensitivity analyses were performed using Cochran’s Q test, MR-Egger intercept, MR-pleiotropy residuals, outlier methods, leave-one-out analysis, and funnel plots. The results showed that there was a causal relationship between heavy DIY and SUI ( OR  = 0.9712, 95% confidence interval [0.951, 0.9918], p  = .006), while no significant causal relationship was found between other physical activities and SUI. These findings were robust across multiple sensitivity analyses. This MR study demonstrates the causal relationship between heavy DIY and SUI, helping doctors and researchers better recommend preventive and treatment measures to patients, while also providing specific directions for improving their lifestyle in men and women suffering from SUI.